Utilizing fuzzy logic to create a prototype robot for load detection - Muhammad Furqon Siregar; Chairul Imam (Jurnal Mantik, 2024)
The application of fuzzy logic in a load-lifting arm robot is covered in this work. Input values are computed using fuzzy logic to prevent inappropriate power usage caused by variations in load weight. The robot's ability to successfully lift the load is the performance that is being evaluated. To choose the motor rotation, the system should calculate the mass of the load. System design is done with an Arduino Uno. For pinching and driving levers, servo motors are used. A mass sensor is used to estimate the mass of the load. Robot construction limits the load to a maximum weight of 900 grams in order to assess robot performance. The findings demonstrate that using Tsukamoto's fuzzy logic model improves accuracy outcomes when determining the degree of slope servo